Optimización de micropartículas por metodología de superficie de respuesta conteniendo aceite por spray drying - Palomino Pérez, Flavia Virginia (2021)
Microencapsulation is presented as an alternative to delay the oxidation of polyunsaturated fatty acids and thus increase the shelf life. The literature indicates spray drying as the most widely used method for encapsulating oils. However, it has some disadvantages, such as the use of high temperatures increases the oxidation of polyunsaturated fatty acids. In this context, spray drying makes it possible to convert a liquid food into a solid. The objective of this study was to optimize the spray drying conditions for sacha inchi oil (Plukenetia volubilis L.) using the response surface methodology. The results indicated that the response corresponding to the response surface model was sufficient to describe and predict the encapsulation efficiency (EE). The effect of the inlet air temperature (160-180 °C) and the combination of GA:INU was evaluated. The microparticles obtained under optimal conditions were characterized, evaluating the parameters of EE, peroxide production, humidity, hygroscopicity and solubility. The EE (83.30 ± 0.01%) was significantly higher and the protection against lipid oxidation after production (6.44 ± 0.19 meq O2 / kg of oil) and after 4 weeks (151.13±1.26 meq O2 / kg of oil) was for the GA(0.854):INU(0.146) system at 162.90 °C. The GA(0.854):INU (0.146) system at 177.10 °C shows the lowest moisture content (2.13 ± 0.64%) and the GA(1):INU(0) system at 170.00 °C the lowest hygroscopicity.